The hidden curriculum in a Filipino pre-service physical educators’ virtual ecology - Ortega, Hans Christian; Castro, Rodel; Tolentino, Julius Ceazar; Pusung, DyjÃ±hlhyn Syrh; Abad, Ronalyn (Edu Sportivo: Indonesian Journal of Physical Education, 2022)
The study was geared toward determining the factors embedded in “hidden curricula” in an online learning environment of a physical education teacher education program. This qualitative-descriptive study considered a complete enumeration of the Bachelor of Physical Education students from a state university in Pampanga, Philippines who voluntarily participated in this qualitative investigation (n = 135) by responding to structured and open-ended questions. Aided by Thematic Analysis, findings revealed six emerging themes that described the embedded hidden curricula in the online learning environment, namely: contributory factors in an online learning experience (OLEx); educational opportunities in the new normal learning set-up; unfavorable factors in using online learning environment; and proposed inputs in enhancing the teaching-learning process in an OLEx. The implications derived as an outgrowth of the identified positive and negative factors as expressed by the participants provided a conceptual understanding of the contemporary picture of the hidden curricula and how it would define the future of an effective online learning experience.